Colorectal cancer screening: factors associated with colonoscopy after a positive faecal occult blood test - Ferrat, E (Nature Publishing Group, 2013)
BACKGROUND: Contextual socio-economic factors, health-care access, and general practitioner (GP) involvement may influence colonoscopy uptake and its timing after positive faecal occult blood testing (FOBT). Our objectives were to identify predictors of delayed or no colonoscopy and to assess the role for GPs in colonoscopy uptake. METHODS: We included all residents of a French district with positive FOBTs (n=2369) during one of the two screening rounds (2007–2010). Multilevel logistic regression analysis was performed to identify individual and area-level predictors of delayed colonoscopy, no colonoscopy, and no information on colonoscopy. RESULTS: A total of 998 (45.2%) individuals underwent early, 989 (44.8%) delayed, and 102 (4.6%) no colonoscopy; no information was available for 119 (5.4%) individuals. Delayed colonoscopy was independently associated with first FOBT (odds ratio, (OR)), 1.61; 95% confidence interval ((95% CI), 1.16–2.25); and no colonoscopy and no information with first FOBT (OR, 2.01; 95% CI, 1.02–3.97), FOBT kit not received from the GP (OR, 2.29; 95% CI, 1.67–3.14), and socio-economically deprived area (OR, 3.17; 95% CI, 1.98–5.08). Colonoscopy uptake varied significantly across GPs (P=0.01). CONCLUSION: Socio-economic factors, GP-related factors, and history of previous FOBT influenced colonoscopy uptake after a positive FOBT. Interventions should target GPs and individuals performing their first screening FOBT and/or living in socio-economically deprived areas.